Analysis of the relationship between change of direction ability, Speed and power in adolescence - Gürkan Diker; Raif Zileli; Hüseyin Özkamçı; Sadi Ön (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2022)
Sprint, change of direction, jump performance plays a major role in success of field-based team sports such as football. This study aims to indicate the relationship between linear sprint (10m, 30m), change of direction (HUFA with and without ball), vertical jump (CMJ) and power (peak power, peak average) parameters in 11-12 years old football players. Thirty-six male football players (average of age 12.55±0.50 years, standing height average 155.63±9.34 cm, body weight average 46.57±8.15, average of years of training 3.58±0.96) from U12 and U13 categories of a football team in Turkish Super League participated in this study. Normality of the data was analysed with the Shapiro-Wilk test and homogeneity of variance was analysed with the Levene test. Statistical analysis of the data obtained were carried out by Pearson Correlation Test as the data was parametric. Statistical significance was accepted as p<0.05. According to the findings, a highly negative significant correlation was found between 10 m and 30 m linear sprint with peak power and average power (p<0.01). There was a moderate, negative significant correlation between change of direction without ball performance and average power (p<0.05). Moderate, negative significant correlation between HUFA change of direction with ball performance and average power was also found (p<0.05). Consequently, leg strength is important and trainings should include drills to improve the leg strength, if sprint speed, maximal speed and quick change of direction speed of the football players in this age group are desired to be improved.